Big Data Analytics for Energy Efficiency - Angelopoulos, Michail; Kontakou, Christina (Archives of Business Research, 2020)
Industries and utilities explore more and more case studies and expert advice concerning the possibilities of intelligent business administration and Big Data analytics. The movement to integrate and meaningfully interpret huge tanks of data points is reaching beyond cutting edge utilities into the mainstream. This project aims at exploring the application of Big Data analytics in the energy sector. Within project’s framework, already developed and operational datasets will be combined with supplemental data from publicly available sources, including prior energy efficiency program participation, enrollment in other energy programs and services, geographic data, customer equipment profiles, demographics, and psychographic customer segmentation categories. There are significant technical, budgetary and project management challenges in undertaking the development and integration of Big Data analytics. There are also organizational challenges in managing change, making decisions in a cooperative framework, and grounding project goals and strategies in the customer experience. The ultimate goal of the project is to develop a reliable database for a step closer to the energy efficiency direction.